Pengelolaan Program Pengabdian bagi Alumni di Pondok Modern Assalam Putri Sukabumi - Elsa Sahara; Nan Rahminawati; Eko Surbiantoro (Bandung Conference Series: Islamic Education, 2024)
Abstract. The output of this service program is to make alumni as prospective educators who have four teacher competencies, namely pedagogic, personality, social, and professional. along with one of the problems of Indonesian education, the quality of teachers. The service program was formed since the beginning of the establishment of Pondok Modern Assalam, there has been no change in all aspects, therefore, the author is interested in how the management of the service program can last a long time, so the author raised the title of the research "Management of Service Programs for Alumni at Pondok Modern Assalam Putri Sukabumi". The purpose of the study is to find program planning, identify program implementation steps, analyze the evaluation carried out on the program, find supporting and inhibiting factors during the service program process. The research method is using qualitative. The data collection techniques used are interviews, observations, and documentation. Data analysis techniques use techniques from Miles and Huberman. The results of the research are the management of service programs is carried out in a structured manner from planning, implementation and evaluation. Program evaluation is carried out by descriptive presentation in the form of report. The supporting factor is the trust given by outside institutions to the resources of Pondok Modern Assalam Putri graduates, from the executive side are asatidzah and ustadzah and service partners. The inhibiting is the transfer of places of service, from the executive side, namely the students, limited time, and parents who do not understand the existing regulations. Abstrak. Output dari program pengabdian ini yaitu menjadikan alumni sebagai calon pendidik yang memiliki empat kompetensi guru yaitu pedagogik, kepribadian, sosial, dan professional. Sejalan dengan salah satu permasalahan pendidikan Indonesia yaitu mengenai kualitas guru. Program pengabdian dibentuk sejak awal berdirinya Pondok Modern Assalam, tidak ada perubahan segala aspeknya, maka dari itu, penulis tertarik akan bagaimana pengelolaan program pengabdian tersebut dapat bertahan lama, sehingga penulis mengangkat judul penelitian “Pengelolaan Program Pengabdian bagi Alumni di Pondok Modern Assalam Putri Sukabumi”. Tujuan penelitian yaitu menemukan perencanaan program, mengidentifikasi langkah-langkah pelaksanaan program, menganalisis evaluasi yang dilaksanakan pada program, menemukan faktor pendukung dan penghambat selama proses program pengabdian. Metode penelitian yaitu menggunakan pendekatan kualitatif. Teknik pengumpulan data yang digunakan yaitu Wawancara, observasi, dan dokumentasi. Teknik analisis data menggunakan Teknik dari Miles dan Huberman. Hasil penelitian yaitu pengelolaan program pengabdian dilaksanakan secara terstruktur dari perencanaan, pelaksanaan dan evaluasi. Evaluasi program dilakukan dengan penyajian deskriptif dalam bentuk laporan. Faktor pendukung selama proses pengabdian yaitu kepercayaan yang diberikan para lembaga luar kepada sumber daya lulusan Pondok Modern Assalam Putri, dari sisi pelaksana yaitu asatidzah dan ustadzah dan rekan satu pengabdian. Penghambat yaitu perpindahan tempat pengabdian, dari sisi pelaksana yaitu para santri, waktu yang terbatas, dan orangtua yang kurang paham atas peraturan yang ada.